2017
DOI: 10.1007/s00726-017-2431-4
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in amino acids lost via sweating could lead to differential susceptibilities to disturbances in nitrogen balance and collagen turnover

Abstract: Fluid collected during sweating is enriched with amino acids derived from the skin’s natural moisturising factors and has been termed “faux” sweat. Little is known about sex differences in sweat amino acid composition or whether faux sweat amino acid losses affect nitrogen balance. Faux sweat collected by healthy adults (n = 47) after exercise, and at rest by chronic fatigue patients, was analysed for amino acid composition. Healthy females had higher total amino acid concentrations in sweat (10.5 ± 1.2 mM) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…de Koning et al (2003) Present in sweat and urine at significantly higher concentrations than found in plasma Dunstan et al (2016Dunstan et al ( , 2017) Source Non-essential as it can be synthesised by the body Serine synthesis can be insufficient to meet body demands leading to sub-optimal growth Maxwell et al (1956) Addition of non-essential serine can instigate improved growth in human cells Eagle (1959) Classified as conditionally essential Histidine Used as the precursor for urocanic acid which is a humectant working as part of the natural moisturising factor on the skin Scott et al (1982), Rawlings and Harding (2004) Is an essential amino acids in humans Required for synthesis of haemoglobin Kopple and Swendseid (1975) Deficit in diet can lead to anaemia Clemens et al (1984), Cooperman and Lopez (2002) Histidine can stabilise oxyhaemoglobin and C)-bound haemoglobin Required for the formation of carnosine Bauchart et al (2007), Tamaki et al (1984) Carnosine is highly concentrated in the muscles and brain Acts as an anti-oxidant, chelating agent, Reddy et al (2005) Acts as an anti-glycating agent to reduce the rate of progression of certain degenerative diseases Hobart et al (2004) Required for the formation of histamine Facilitates inflammatory immune response Stimulates gastric secretion Neurotransmission roles Nieto-Alamilla et al (2016) Histidine is a major component in actin and myosin families of muscle proteins Methylated to form 3-methyl-histidine Anti-inflammatory and anti-secretory properties Histidine acts as an anti-oxidant by scavenging the hydroxyl radical and singlet oxygen Raghavan et al (1989), Wade and Tucker (1998) Present in sweat and urine at significantly higher concentrations than found in plasma Dunstan et al (2016Dunstan et al ( , 2017 Activated sympathetic neurotransmission to adipose tissues and accelerated energy expenditure Konishi et al (2015) Decreased food intake (appetite suppression) Increased fat utilisation in brown adipose tissue Present in sweat at significantly higher concentrations than found in plasma Dunstan et al (2016) Source Non-essential as it can be synthesised by the body Ornithine synthesis can be insufficient to meet body demands leading to Sub-optimal nitrogen excretion Inefficient energy metabolism Could be classified as conditionally essential…”
Section: Serinementioning
confidence: 96%
See 4 more Smart Citations
“…de Koning et al (2003) Present in sweat and urine at significantly higher concentrations than found in plasma Dunstan et al (2016Dunstan et al ( , 2017) Source Non-essential as it can be synthesised by the body Serine synthesis can be insufficient to meet body demands leading to sub-optimal growth Maxwell et al (1956) Addition of non-essential serine can instigate improved growth in human cells Eagle (1959) Classified as conditionally essential Histidine Used as the precursor for urocanic acid which is a humectant working as part of the natural moisturising factor on the skin Scott et al (1982), Rawlings and Harding (2004) Is an essential amino acids in humans Required for synthesis of haemoglobin Kopple and Swendseid (1975) Deficit in diet can lead to anaemia Clemens et al (1984), Cooperman and Lopez (2002) Histidine can stabilise oxyhaemoglobin and C)-bound haemoglobin Required for the formation of carnosine Bauchart et al (2007), Tamaki et al (1984) Carnosine is highly concentrated in the muscles and brain Acts as an anti-oxidant, chelating agent, Reddy et al (2005) Acts as an anti-glycating agent to reduce the rate of progression of certain degenerative diseases Hobart et al (2004) Required for the formation of histamine Facilitates inflammatory immune response Stimulates gastric secretion Neurotransmission roles Nieto-Alamilla et al (2016) Histidine is a major component in actin and myosin families of muscle proteins Methylated to form 3-methyl-histidine Anti-inflammatory and anti-secretory properties Histidine acts as an anti-oxidant by scavenging the hydroxyl radical and singlet oxygen Raghavan et al (1989), Wade and Tucker (1998) Present in sweat and urine at significantly higher concentrations than found in plasma Dunstan et al (2016Dunstan et al ( , 2017 Activated sympathetic neurotransmission to adipose tissues and accelerated energy expenditure Konishi et al (2015) Decreased food intake (appetite suppression) Increased fat utilisation in brown adipose tissue Present in sweat at significantly higher concentrations than found in plasma Dunstan et al (2016) Source Non-essential as it can be synthesised by the body Ornithine synthesis can be insufficient to meet body demands leading to Sub-optimal nitrogen excretion Inefficient energy metabolism Could be classified as conditionally essential…”
Section: Serinementioning
confidence: 96%
“…Represents 11.5% of all amino acids Wu (2010a, b) Represents 20% of the amino acids in proteins Represents 33% of amino acids in collagen which is the most abundant family of proteins in the body Wu (2009) Used as a humectant in the natural moisturising factor in the skin Scott et al (1982) Inhibitory nerve transmitter Rajendra et al (1997) Glycine modulates Ca 2+ levels in leukocytes and macrophages regulating the production of cytokines, and the generation of superoxide for immune function Zhong et al (2003) Conjugation with bile acids with a key role in digestion and absorption of fatty acids, lipophilic nutrients and lipid-soluble vitamins Hafkenscheid and Hectors (1975) Found in major pathways of metabolism Hall (1998) Purines for generating nucleosides, nucleotides, RNA and DNA Haem for haemoglobin and cytochromes critical for oxygen transport/CO 2 removal and mitochondrial electron transport Dai et al (2013) Creatine which participates in energy metabolism within muscles and nerves Glutathione which is the most abundant low molecular weight thiol and the major anti-oxidant in cells Wu et al (2004) Present in sweat and urine at significantly higher concentrations than found in plasma Dunstan et al (2016Dunstan et al ( , 2017) Source It is technically classified as non-essential as it can be synthesised by the body Darling et al (1999), Wu (2010a) Glycine synthesis can be insufficient to meet body demands leading to sub-optimal growth, impaired immune responses…”
Section: Glycinementioning
confidence: 99%
See 3 more Smart Citations